Conduction Type Control of Ge-on-Insulator: Combination of Smart-Cut™ and Defect Elimination. (22nd October 2019) - Yamamoto, Keisuke; Nakae, Kohei; Akamine, Hiroshi; Wang, Dong; Nakashima, Hiroshi; Alam, Md. M; Sawano, Kentarou; Xue, Zhongying; Zhang, Miao; Di, Zengfeng
Abstract : We electrically characterized Ge-on-Insulator (GOI) fabricated by Smart-Cut™ method. Annealing improved electrical characteristics of the p-GOI. On the other hand, conduction type of the n-GOI changed to p-type after annealing. Structural analysis showed many defects were introduced near the bottom interface and it cannot be recovered by annealing. We suggest alternative ways to avoid defects for n-GOI fabrication.